An assessment of the effectiveness of Integrated Reporting in improving financial performance of companies listed on the Zimbabwe Stock Exchange - Mandingaisa, Michael (Midlands State University, 2018)
Corporate scandals have disturbed the business community world over in the past. The stakeholders now demand specific reports with improved disclosure and transparency to safeguard their interests in any organization. The companies listed on the Zimbabwe Stock Exchange (ZSE) are largely reporting on financial content in their annual reports. In-roads have been made to embrace integrated reporting which is a comprehensive financial reporting framework. Integrated reporting forms part of the non-financial information which has more disclosures and is more transparent about the strategy, risk management and long-term planning of top management. Integrated reporting links together the critical themes of sustainability, corporate governance, strategic planning and social responsibility activities. Organizations have invested into integrated reporting and implemented the reporting framework with the hope of guaranteed financial performance. This research study analyze whether integrated reporting is effective in improving the financial performance of companies listed on the ZSE.